Retinoblastoma: Evolving Concepts and Future Challenges - Wiekiera, Mateusz; Jasiuk, Adrianna; Madeja, Natalia; Koziej, Sylwia; Niemczuk, Martyna; Kowalczyk, Emilia (Quality in Sport, 2025)
Retinoblastoma is the most common ocular malignancy in children. It results from mutations in the RB1 gene or from MYCN oncogene amplification. We distinguish between the more common unilateral form and the rarer bilateral form. It is important to note that bilateral retinoblastoma is always hereditary. The most common and characteristic symptom is the white pupillary reflex. In addition, the child may develop strabismus or heterochromia. Treatment methods vary, ranging from those aimed at salvaging the eye to those involving total enucleation. Prognosis depends on the location and stage of the tumor. This review aims to explore the literature on new therapeutic methods and recent discoveries in the field of retinoblastoma.